Manajemen Pengetahuan Salah Sebagai Satu Jalan Dalam Pengembangan Lembaga Pendidikan Unggul Pada Tk Bina Mulia Cibitung - Dwi Budi Srisulistiowati; Khaerudin, Muhamad; Warta, Joni (Journal of Informatic and Information Security, 2020)
Along with the significant development of life progress, the competition that occurs requires people to follow the flow of adjustments as well as the world of education which now provides many alternative choices and levels of quality. Educational institutions need to develop their competitive advantage in order to survive, compete and sustain their survival properly. The resources needed to maintain its survival are not solely from traditional resources but must also come from intangible resources, namely knowledge. To benefit from the knowledge they have and what knowledge they must have, educational institutions / organizations must manage their knowledge through knowledge management. Consciously, educational institutions must know the knowledge they have and their benefits to improve performance and increase innovation and creativity. To achieve superior educational institutions, knowledge management is needed, namely the ability to create and maintain value that is greater than the competitiveness of the core institution. Knowledge and experience are able to create, communicate and apply knowledge about various things to achieve organizational goals, namely to become a superior educational institution.